PENGARUH PAJAK, TUNNELING INCENTIVE, DEBT COVENANT DAN PROFITABILITAS TERHADAP KEPUTUSAN MELAKUKAN TRANSFER PRICING - Ahmad Junaidi; Nensi Yuniarti. Zs (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to determine the effect of taxes, tunneling incentives, debt covenants, and profitability on the company's decision to transfer pricing. The data used in this study is secondary data obtained from accessing the web www.idx.co.id. The population of this research was manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The sampling technique used was purposive sampling. The number of companies sampled in the study was 27 companies so that the total sample of the study was 135 observations. This study used the multiple linear regression analysis technique. The results of this study known there are still many variables outside the research that can explain transfer pricing.The determination coefficient is 0.441 which means that 44.1%. It indicates that the company transfers pricing is influenced by these variables, while the rest is explained by other variables.Based on theÂ result can be concluded that taxes, debt covenants and profitability has a positive effect on the decision to transfer pricing. While the tunneling incentive does not effect the decision to conduct transfer pricing.Keywords: Tax, Tunneling Incentive, Debt Covenant, Profitability, and Transfer Pricing